PENINGKATAN PERKEMBANGAN MOTORIK HALUS MELALUI TEKNIK MOZAIK PADA ANAK USIA 5-6 TAHUN DI TK NEGERI 2 AIKMEL - Jayanti, Baiq Napisahtul Putri; Nurhasanah; Astawa, I Made Suwasa; Astini, Baik Nilawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study was to determine the improvement of children's fine motor development by using mosaic techniques in children aged 5-6 years at TK Negeri 2 Aikmel. The type of research used is Classroom Action Research (PTK). The subjects studied in this study were 18 children aged 5-6 years and 1 teacher, data collection techniques in the form of observation and documentation. This research uses descriptive data analysis method. The results showed that in cycle I, the application of the implementation of the mosaic technique received an average score of 31.5 with a percentage result of 71% which included the implemented category, while the increase in children's fine motor development received an average score of 731 with a percentage result of 68% with the category developing as expected, while in cycle II the application of the implementation of the mosaic technique received an average score of 39, 5 with a percentage result of 89.7% with a well-implemented category, and in the improvement of children's fine motor development, the average score is 922.5 with a percentage result of 85.2% with a very well-developed category so that it can be concluded that the improvement of fine motor development of children aged 5-6 years at TK Negeri 2 Aikmel can increase through the mosaic technique.